Implementing Artificial Intelligence in Media Production A Field Research on a sample of local media outlets in Setif (Revue El-Wahat pour les Recherches et les Etudes, 2025)
This research paper aims to investigate the extent to which artificial intelligence is used in the journalistic production process within local media institutions, specifically in the city of Setif, Algeria. Given the widespread use of artificial intelligence in all economic and media sectors globally due to its facilitation and acceleration of performance, the application of artificial intelligence is generally subject to the extent to which the institutional environment, with all its cultural, social, and scientific components, can accept artificial intelligence performance. This descriptive survey study attempts to explore the extent of artificial intelligence use within journalistic institutions through: the artificial intelligence techniques employed in the editorial and journalistic production process and its reliance on improving technical processes within institutions and their management, the use of artificial intelligence in data analysis to provide audience-related insights and assist in making strategic decisions in local media institutions, and the extent to which the studied journalistic institutions rely on training employees on artificial intelligence techniques to keep pace with developments at the international and global levels. The study concludes that there are many challenges facing efforts to expand the scope of work with artificial intelligence, primarily due to the technological capabilities of institutions and their readiness to implement artificial intelligence. Additionally, the digital culture of the workforce is a significant obstacle to accepting the idea of delegation or replacement by programs and robots.Keywords: Artificial Intelligence, Media Organizations,Journalistic Production